2019
DOI: 10.1039/c9ee01591d
|View full text |Cite
|
Sign up to set email alerts
|

Searching for stability at lower dimensions: current trends and future prospects of layered perovskite solar cells

Abstract: Two-dimensional perovskites are an attractive alternative to 3D perovskites for solar cell application as they directly address a critical issue of stability of 3D perovskite solar cells, while achieving similarly high power conversion efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 205 publications
3
103
0
Order By: Relevance
“…To tackle this problem, one of the proposed solutions is to use 2D perovskites such as those of the Ruddlesden-Popper family to increase the stability with respect to moisture. 6,7 Mixing compositions of 2D/3D LHPs has been shown to increase the stability while maintaining a good performance. 8,9 These lower dimensionality perovskites are obtained by introducing larger cations into the precursor mix.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this problem, one of the proposed solutions is to use 2D perovskites such as those of the Ruddlesden-Popper family to increase the stability with respect to moisture. 6,7 Mixing compositions of 2D/3D LHPs has been shown to increase the stability while maintaining a good performance. 8,9 These lower dimensionality perovskites are obtained by introducing larger cations into the precursor mix.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid perovskite solar cells (PVSCs) have been regarded as a promising candidate for next‐generation photovoltaics (PVs) due to their various unique properties, including high absorption coefficients, large charge carrier mobilities, long electron/hole diffusion lengths, facile solution processability, and low fabrication cost . However, the volatile nature of organic cations such as methylammonium (MA + ), formamidinium (FA + ), and so on in these perovskites causes some stability issues under the light, photo, and thermal stresses . Alternatively, inorganic cations such as Cs + ions have been reported that can potentially replace organic cations to address these stability issues .…”
Section: Best and Average (Reverse Scan) Pv Parameters Measured In Rementioning
confidence: 99%
“…Another concept is the use of bulkier hydrophobic organic cations to replace the hygroscopic MA and FA organic ions. Due to tolerance factors, the use of a large bulkier organic cation results in the transformation of the 3D perovskites into the 2D layered perovskite structure, which is environmentally more stable [60,61]. Although more efforts to enhance device efficiency are required [62], the adoption of 2D/3D hybrid structures or 2D interlayers is promising routes to explore the advantages of both types of perovskites.…”
Section: D Pscsmentioning
confidence: 99%